2002
DOI: 10.1152/ajpheart.00313.2002
|View full text |Cite
|
Sign up to set email alerts
|

Defective intracellular Ca2+ signaling contributes to cardiomyopathy in Type 1 diabetic rats

Abstract: The goal of the study was to determine whether defects in intracellular Ca(2+) signaling contribute to cardiomyopathy in streptozotocin (STZ)-induced diabetic rats. Depression in cardiac systolic and diastolic function was traced from live diabetic rats to isolated individual myocytes. The depression in contraction and relaxation in myocytes was found in parallel with depression in the rise and decline of intracellular free Ca(2+) concentration ([Ca(2+)](i)). The sarcoplasmic reticulum (SR) Ca(2+) store and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
224
2
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(269 citation statements)
references
References 34 publications
33
224
2
8
Order By: Relevance
“…These alterations are the result of changes in the expression and function of SR Ca 2+ handling proteins; SERCA2a, NCX and RyR expressions are reduced, whereas phospholamban expression is increased and its phosphorylation decreased. As a consequence, SR Ca 2+ load is reduced, and SR Ca 2+ release and re-uptake are impaired [181,182]. Interestingly, an increased [184,185].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…These alterations are the result of changes in the expression and function of SR Ca 2+ handling proteins; SERCA2a, NCX and RyR expressions are reduced, whereas phospholamban expression is increased and its phosphorylation decreased. As a consequence, SR Ca 2+ load is reduced, and SR Ca 2+ release and re-uptake are impaired [181,182]. Interestingly, an increased [184,185].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…The oxidative stress can impair glucose transport/utilization as well as mitochondrial ATP generation and intracellular Ca 2+ regulatory proteins. Abnormalities in Ca 2+ signaling/flux and myofilament functions, contribute to the cardiomyopathy changes and defective cardiac contractile function (86)(87). In the 1980s, Przyklenk K et al demonstrated that superoxide dismutase (SOD) plus catalase improve myocardial contractile function in the canine model (88).…”
Section: Cardiac Mitochondria Abnormalities and Ros Elevationmentioning
confidence: 99%
“…The speed of contraction of cardiomyocytes is controlled by proteins that regulate intracellular Ca 2+ movement and the rate of ATP hydrolysis which, in turn, regulates the rate of formation of crossed bridges 21 . Cardiomyocytes of diabetic animals reduce the expression of regulatory proteins such as CaMKII, NCX, RyR2, SERCA2 and phospholamban (PLB) 5,7,15,[24][25][26] , which may delay the availability of Ca 2+ for cell contraction.…”
Section: Figure 1 -Contractile Function Of Cardiomyocytes Of Control mentioning
confidence: 99%
“…by SR, which helps to slow down cell relaxation 26 . These findings at the cellular level are consistent with the diastolic dysfunctions observed in diabetic hearts in vivo 7,11 .…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation